Hemophagocytic Lymphohistiocytosis in a Patient with Classical Hodgkin Lymphoma - G. Hyun; K. J. Robbins; N. Wilgus; L. Grosso; S. D. Goyal (Case Reports in Hematology)
Introduction. Hemophagocytic lymphohistiocytosis (HLH) is a rare hyperinflammatory syndrome that can be associated with inherited genetic mutations, malignancy, autoimmune disorders, and viral infections. Though the pathogenesis is not fully known, HLH is understood to be a reactive process in the setting of uncontrolled activation of macrophages, CD8+ cytotoxic lymphocytes, and other immune cells. Hallmark clinicopathological features of HLH include fevers, cytopenias, hepatosplenomegaly, and hemophagocytosis in the bone marrow. Case Presentation. A previously healthy 28-year-old Caucasian male presented with a one-month history of persistent fever, night sweats, and unintentional weight loss. He was diagnosed with classical Hodgkin Lymphoma (HL) by core-needle biopsy of an axillary lymph node. Both bone marrow involvement by HL and hemophagocytosis were seen on subsequent bone marrow biopsy. Other findings included pancytopenia, splenomegaly, and elevated serum ferritin. Extensive work-up for autoimmune and infectious etiologies was unremarkable. The patient had a complete response after chemotherapy with Adriamycin, bleomycin, vincristine, and dacarbazine. Conclusion. This report documents the exceedingly uncommon association between HLH and HL. HLH is a hyperinflammatory syndrome with high mortality, so it is imperative to identify and treat the underlying cause for secondary HLH. Malignancy-associated HLH should be considered in the differential diagnosis for cancer patients who present with fever, cytopenias, and splenomegaly.